Pengaruh Model Hybrid Learning Terhadap Hasil Belajar Siswa Kelas XI Pada Mata Pelajaran Fiqih Di MA Mambaul Ulum Megaluh Jombang - Kris Yuan Hidayatullah, Muhammad; Nisa', Evita Faridhotun; Putra, Ino Angga (Universitas KH. A. Wahab Hasbullah, 2023)
In this modern era, education is very important for human development and progress. Education cannot be separated from the so-called learning process. One of the achievements of educational goals can be seen from the learning outcomes of a student after going through the learning process he does. Hybrid learning is a combination of the learning process in the classroom with online learning or outside the classroom, to take advantage of existing technological tools in the current era. During the COVID-19 pandemic emergency that occurred throughout the world in 2019-2021, problems occurred, especially in education and finally learning activities were transferred online. The purpose of this study was to determine the effect of the hybrid learning model on the learning outcomes of class XI students in fiqh subjects at MA Mambaul Ulum Megaluh Jombang. Data collection techniques using tests in the from of multiple choice questions pre-test and post-test, validation sheets. Researchers used the Pre-Experimental Desain and Paired Sample Test menthods to determine the effect on student learning outcomes. The results of the research that have been carried out state that the average of all aspects is 88.796%, which means it is very feasible to use research at MA Mambaul Ulum Megaluh Jombang. Student learning outcomes using the pre-test and post-test, the students’ average score was 52.8% for the pre-test score and for the post-test score the students’ average score was 69.5%. The significant value is <0.05 in the Pairet Sample Test table. This means that there is a significant effect on student learning outcomes in fiqh class XI subjects at MA Mambaul Ulum Megaluh Jombang, on the treatment given during the pre-test and post-test. Keywords: Hybrid Learning Model, Student Learning Outcome, Fiqih Mawaris